The Influence of Interpersonal Communication, Universal-Diverse Orientation (UDO), and Self-Efficacy on the Quality of Administrative Services at State University of Jakarta - Ifatuhoriah Yusuf; Dedi Purwana; Agung Dharmawan Buchdadi (Bright Institute, 2022)
This study aims to determine the direct effect of interpersonal communication, universal-diverse orientation (UDO), and self-efficacy on the quality of administrative services, as well as to determine the indirect effect of interpersonal communication and universal-diverse orientation (UDO) through self-efficacy on the quality of administrative services at State University of Jakarta. The research used was a survey with a causal design. The number of sample respondents was determined as 178 employees, the sampling technique was carried out by simple random (sample random sampling) from 230 employees of the State University of Jakarta. The results of this study indicate that; (1). There is a positive direct effect of Interpersonal Communication on the Quality of Academic Services, (2). There is a positive direct influence Universal-Diverse Orientation (UDO) on the Quality of Academic Services, (3). There is a positive direct effect of Self Efficacy on Academic Service Quality., (4) There is a positive direct influence of Interpersonal Communication on Self Efficacy, (5) There is a positive direct influence of Universal-Diverse Orientation (UDO) on Self Efficacy. The novelty in this research is that research conducted at this time is research looking at several variations of variables such as the influence of interpersonal communication, universal-diverse orientation (UDO), and self-efficacy on the quality of administrative services and quality variables as independent variables.